SQUARE WAVE CATHODIC STRIPPING VOLTAMMETRY ADSORPTIVE FOR NICKEL AND COBALT ANALYSIS - Saryati Saryati; Sumardjo Sumardjo (Universitas Gadjah Mada, 2006)
The adsorptive stripping voltammetric determination of Ni and Co based on adsorption of the Ni/Co and dimethylglioxime (DMG) complex on a hanging mercury drop electrode is studied. The reduction current of the adsorbed DMG complex is measured by square wave cathodic stripping voltammetry method. The effect of various parameters such as ligand concentration, pH of supporting electrolytic, adsorption potential and adsorption time on the current peak of Ni and Co voltammogram were studied. Optimum condition of this method are supporting electrolyte pH 9, DMG concentration 5×10 -4 M, adsorption potential -0.7 V vs Ag/AgCl and adsorption time 180 second. A linier relationship between the current peak and Ni or Co concentration was obtained in the range 5 - 30 ng/mL and the detection limit 0.6 ng/ml for both Ni and Co. The recovery of Ni and Co were 98.11-104.17% using standard biological materials with RSD 2.59 - 10.37%. Based on